THE ESSENCE OF RELIGION IN THE PERSPECTIVE OF ISLAMIC MYSTICISM - Esmaeili, Masoud (Sekolah Tinggi Filsafat Islam (STFI) Sadra, 2012)
â€œThe Essence and Shell of Religionâ€ is a philosophico-theological problem which is Occidental in its context. â€œReligious Experienceâ€ and â€œSophia Perennisâ€ are two mooted theories on this issue. h e essence of religion, according to fi rst theory, lies in the experience that makes its possessor to be seen religious and the shell is a set of beliefs that has its origin in the independence that the wayfarer feels after touching the essence and the second theory defines religion as a bisurfi cial phenomenon whose inward surface is monotheism which is manifested in the form of Sophia Perennis inside human being and the shell is consisted of traditions that leads the wayfarer toward the gem. In Islamic mysticism, religion is an integrated and seamless truth that has triple manifestations of exoteric, esoteric and ultra-esoteric. The esoteric manifestation is the individual unity which is also the gem of religion, though they are seen as the shell exoteric manifestations are merely diluted shadows of the same esoteric truth and thus they are imperishable. Religiosity is also a threefold truth whose essence is the absolutely certain intuition of mystic monotheism; and thus conceived, religion and religiosity are coextensive in their essence.Â